Simulasi Analisis Kualitas Daya Menggunakan Logika Fuzzy Untuk Meningkatkan Efisiensi Sistem Tenaga Listrik - Fernando Wibisono; Tamaji (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
This study aims to simulate power quality analysis using fuzzy logic to increase the efficiency of the power system. Poor power quality can cause disturbances in the electric power system and reduce the efficiency of the energy used. Therefore, improving power quality is one of the main focuses in the electric power industry.The fuzzy logic method is used in this study to evaluate power quality based on relevant parameters, such as voltage, current, frequency and harmonics. Fuzzy logic is able to overcome the uncertainty and complexity of data related to electric power systems, and provide more adaptive and intelligent solutions. In this study, simulations were carried out using special software that implements fuzzy logic to analyze power quality. The input data obtained from the electric power system is used to build a fuzzy logic model. Then, the simulation results are used to identify existing power quality problems and propose appropriate improvement strategies.The simulation results show that the use of fuzzy logic can significantly increase the efficiency of the power system by minimizing disturbances and optimizing power quality. In addition, fuzzy logic also provides the ability to predict the future conditions of the electric power system and take the necessary precautions. This research has important practical implications in the field of power systems. By using fuzzy logic in power quality analysis, power companies and grid operators can optimize power system operations, reduce power losses, improve energy efficiency, and ensure reliable electricity supply to consumers.